Progress in antischistosomal N, N′-diaryl urea SAR. Issue 3 (1st February 2018) - Wu, Jianbo; Wang, Chunkai; Leas, Derek; Vargas, Mireille; White, Karen L.; Shackleford, David M.; Chen, Gong; Sanford, Austin G.; Hemsley, Ryan M.; Davis, Paul H.; Dong, Yuxiang; Charman, Susan A.; et al.
Graphical abstract: Highlights: Expansion of antischistosomal N, N ′-diaryl urea SAR. 3-Trifluoromethyl-4-pyridyl and 2, 2-difluorobenzodioxole improve exposure. 4-Fluoro-3-trifluoromethylphenyl required for best antischistosomal activity. Abstract: N, N ′-Diaryl ureas have recently emerged as a new antischistosomal chemotype. We now describe physicochemical profiling, in vitro ADME, plasma exposure, and ex vivo and in vivo activities against Schistosoma mansoni for twenty new N, N ′-diaryl ureas designed primarily to increase aqueous solubility, but also to maximize structural diversity. Replacement of one of the 4-fluoro-3-trifluoromethylphenyl substructures of lead N, N ′-diaryl urea1 with azaheterocycles and benzoic acids, benzamides, or benzonitriles decreased lipophilicity, and in most cases, increased aqueous solubility. There was no clear relationship between lipophilicity and metabolic stability, although all compounds with 3-trifluoromethyl-4-pyridyl substructures were metabolically stable. N, N ′-diaryl ureas containing 4-fluoro-3-trifluoromethylphenyl, 3-trifluoromethyl-4-pyridyl, 2, 2-difluorobenzodioxole, or 4-benzonitrile substructures had high activity against ex vivo S. mansoni and relatively low cytotoxicity. N, N -diaryl ureas with 3-trifluoromethyl-4-pyridyl and 2, 2-difluorobenzodioxole substructures had the highest exposures whereas those with 4-fluoro-3-trifluoromethylphenyl substructures had the best in vivo antischistosomal activities. There was no direct correlation between compound exposure and in vivo activity.